Analisis Peran Pengembangan Karir dalam Memediasi Pengaruh Pendidikan dan Pelatihan terhadap Kinerja Pegawai : Studi pada Pengadilan Tinggi Jawa Tengah - Sarah Fitria Damara; Suhana Suhana (Journal of Management and Creative Business, 2026)
This study aims to analyze the role of career development in mediating the effects of education and training on employee performance at the Central Java High Court. This research was motivated by the importance of improving employee performance through education and training, as well as the need for an effective career development system to optimize their impact. This study employed a quantitative approach. The population consisted of 141 civil servants at the Central Java High Court, with a sample of 94 non-judge civil servants selected using purposive sampling. Data were collected through a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. The results showed that education and training had no significant direct effect on employee performance. However, education and training had positive and significant effects on career development, while career development had a positive and significant effect on employee performance. Furthermore, career development fully mediated the effects of both education and training on employee performance. These findings imply that education and training can improve employee performance indirectly through effective career development. Therefore, organizations should strengthen career development systems to optimize the benefits of education and training and support sustainable improvements in employee performance.